Relationship of foraminiferal abundance with the trophic conditions in a marine coastal area of western India - Avilavalappil, Amrutha; Patil, Rajashekhar K.; Hiriyur Mallaiah, Somashekarappa (Scientia Marina, 2014)
Surface seawater and sediment parameters indicate the trophic state of coastal marine systems. We used a biochemical approach to identify descriptors of the trophic state and environmental quality of intertidal ecosystems, based on the analysis of the quality and quantity of sedimentary organic matter, water nutrients and their correlation with the foraminiferal population at two sites on the west coast of India. Surface intertidal sediments were collected for a period of 17 months from January 2012 to May 2013 at intervals of two months by using a short core tube. Total foraminiferal number and live foraminiferal number showed a peak during the post-monsoon period, when there is an enrichment of sediment chlorophyll a as well as a dominance of carbohydrates over sedimentary protein. Thus, a small change in the trophic status of the environment from a lower oligotrophic to a higher oligotrophic condition is responsible for the enhancement of foraminiferal population and diversity in the study sites. In particular, sediment protein concentration appeared to be a good descriptor of the trophic state. A gradual increase in foraminiferal population from a protein-rich, fresh organic matter environment to a carbohydrate-rich, detritus organic matter environment indicates the foraminiferal preference for detritus food sources. Thus, the main regulation factor for abundance and diversity of foraminifera at the study sites is trophication.